2019
DOI: 10.3390/antiox8090338
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Melatonin Supplementation in Women with Unexplained Infertility Undergoing Fertility Treatment

Abstract: Unexplained infertility occurs when common causes for a couple’s inability to conceive have been excluded. Although origins of idiopathic infertility are still unclear, factors, such as an altered oxidative balance, are believed to be involved. Melatonin is an outstanding antioxidant reportedly present in the follicular fluid (FF), which has been suggested as a useful tool in the management of human fertility. Herein, we observed that intrafollicular concentrations of melatonin were blunted in women with unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 40 publications
2
44
0
4
Order By: Relevance
“…The PRISMA flow diagram of the review process was presented in Figure 1. A total of 10 randomized trials were included for analysis (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Characteristics of the included studies were presented in Tables 1, 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The PRISMA flow diagram of the review process was presented in Figure 1. A total of 10 randomized trials were included for analysis (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Characteristics of the included studies were presented in Tables 1, 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nine studies reported the effect of melatonin on clinical pregnancy in IVF/ICSI-ET cycles (18)(19)(20)(21)(23)(24)(25)(26)(27). Meta-analysis suggested that melatonin treatment significantly increased clinical pregnancy rate [OR = 1.39 (1.05, 1.84), P < 0.05].…”
Section: Clinical Pregnancy Per Allocated Woman In Ivf/icsi-et Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the administration of melatonin to patients suffering from infertility increases follicular concentrations of melatonin, which thereby inhibits oxidative stress and improves the quality of oocytes, thus improving fertilization and pregnancy rates. After this initial study, other reports also examined whether melatonin therapy improves the clinical outcome of IVF-ET, with the findings likewise also showing that the concurrent use of melatonin increases the number of mature oocytes, the fertilization rate, and number of high-quality embryos [39,[46][47][48][49][50] (Table 1). It is suggested that the effects of melatonin include an increased concentration of melatonin in the follicular fluid and a reduced 8-OHdG concentration, which leads to the conclusion that melatonin's multiple antioxidant actions lower oxidative stress in oocytes [39,50].…”
Section: Melatonin In Assisted Reproductive Technology (Art)mentioning
confidence: 99%
“…These intriguing findings are consistent with the view that pharmacological melatonin administration increases intra-follicular melatonin concentrations, reduces intra-follicular oxidative damage and may have a beneficial effect on fertilization and pregnancy rates during ART. In a recent report, similar benefits were found in 40 women with idiopathic infertility who were administered pharmacological melatonin and who subsequently showed improved intrafollicular oxidative capacity and oocyte quality in IVF protocols (58).…”
Section: Melatonin and The Female Reproductive Cyclementioning
confidence: 56%